Analisis Perbandingan Keuntungan dan Risiko Usaha Perikanan Rakyat Sistem Monokultur dan Polikultur di Kabupaten Pangkep - Tsalis Kurniawan Husain; Jangkung Handoyo Mulyo; Jamhari Jamhari (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2016)
The purpose of this research is to analyze and compare the cost, profit, and risk of monoculture and polyculture fisheries system in Pangkep Regency. The sample collection uses the snowball sampling method. There are 80 fish farmers who were interviewed in this research. The cost and income is analyzed by income analysis, while to measure the level of business risk, Coefficients Variation (CV) analysis is used. To test the hypothesis, analysis of z distribution test is used. The research results show that the fishing cost and income of polyculture system is larger than monoculture system, where the cost of each is Rp 14.722.597 and Rp 13.191.880 respectively, while their profit is Rp 10.285.066 and Rp 6.710.486 each. Polyculture system has cost risk, revenue risk and profit risk is lower than monoculture system with large value of Coefficients Variation (CV) each by 0,11; 0,29 and 0,56 for polyculture system and 0.12; 0,37 and 0,88 for monoculture system. The results of the hypothesis showed that there is difference in cost of, revenue, and profit between poliyculture and monoculture system while there is no significance difference for cost risk, revenue risk and profit risk.